2014
DOI: 10.1097/01.tp.0000437433.35227.77
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Avoidance in Pediatric Heart Transplantation Results in Excellent Graft Survival

Abstract: Background Maintenance steroid (MS) use in pediatric heart transplantation (HT) varies across centers. The purpose of this study was to evaluate the impact of steroid-free maintenance immunosuppression (SF) on graft outcomes in pediatric HT. Methods Patients younger than 18 years in the United States undergoing a first HT during 1990 to 2010 were analyzed for conditional 30-day graft loss (death or repeat HT) and death based on MS use by multivariable analysis. A propensity score was then given to each patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In our analysis, it was unclear why mid‐term rates of hypertension, dyslipidemia, and bone disease were higher among patients in whom CS were withdrawn early; it is possible, however, that attempts to wean CS were made in this subgroup due to pre‐existing clinical features for such complications. In pediatric heart transplant recipients, strategies to decrease CS exposure early post‐transplant have been evaluated in a large contemporary cohort and demonstrated a decrease in complications without compromising graft or patient survival . Our study provides a further incentive to pro‐actively decrease the long‐term use of CS in adult transplant recipients.…”
Section: Discussionmentioning
confidence: 82%
“…In our analysis, it was unclear why mid‐term rates of hypertension, dyslipidemia, and bone disease were higher among patients in whom CS were withdrawn early; it is possible, however, that attempts to wean CS were made in this subgroup due to pre‐existing clinical features for such complications. In pediatric heart transplant recipients, strategies to decrease CS exposure early post‐transplant have been evaluated in a large contemporary cohort and demonstrated a decrease in complications without compromising graft or patient survival . Our study provides a further incentive to pro‐actively decrease the long‐term use of CS in adult transplant recipients.…”
Section: Discussionmentioning
confidence: 82%
“…Much has been done in minimising immunosuppression in children such as lowering targeted calcineurin inhibitor levels and steroid use, but not enough has been done to study lessening invasive monitoring by endomyocardial biopsy. 39,40 This study provides the first description of outcomes of a low-intensity biopsy surveillance protocol integrated with standardised clinical/echocardiographic monitoring across paediatric age groups in a contemporary era. In this study, our patient population experienced similar aggregate outcomes across both a short and intermediate term in relation to what is reported in registries.…”
Section: Discussionmentioning
confidence: 99%
“…23 Multiple registry analyses have reported that corticosteroids can be avoided in children with excellent freedom from rejection and overall post-transplant survival outcomes. [24][25][26] More recently, a multicenter, prospective, cohort study reported 1-year outcomes among recipients without pretransplant donor-specific antibodies (DSAs) who received induction with anti-thymocyte globulin (ATG), peri-operative steroids, and maintenance immunosuppression with tacrolimus and/or mycophenolate mofetil and managed with a steroid-free protocol had excellent short-term survival (94.5%). 27 The majority of pediatric heart transplant programs still give methylprednisolone in the perioperative period for 2-5 days (typically as pre-medication with induction therapy) followed by a rapid wean to either low-dose maintenance steroids or a steroid-free regimen.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Prednisone use in children is decreasing with ISHLT registry data revealing that 66% of recipients were discharged on prednisone in the most recent era (January 2010—June 2018) compared to 74% in the previous era (January 2005—December 2009) 23 . Multiple registry analyses have reported that corticosteroids can be avoided in children with excellent freedom from rejection and overall post‐transplant survival outcomes 24‐26 . More recently, a multicenter, prospective, cohort study reported 1‐year outcomes among recipients without pre‐transplant donor‐specific antibodies (DSAs) who received induction with anti‐thymocyte globulin (ATG), peri‐operative steroids, and maintenance immunosuppression with tacrolimus and/or mycophenolate mofetil and managed with a steroid‐free protocol had excellent short‐term survival (94.5%) 27 .…”
Section: The Evolution Of Immunosuppressionmentioning
confidence: 99%